How could you - Strapp, Ren (Oni Press : Oni-Lion Forge Publishing Group, LLC, 2024)
"College upperclassman Molly Song is set on getting over her ex this semester, but it's hard when she dumps you via email and posts all over social media about cozying up with her study-abroad roommate. After convincing her friend, Lou Kingston, that they should go to parties and find rebound girlfriends, Molly learns she should be careful what she wishes for when she starts to develop real feelings for someone she's not sure feels the same way. Meanwhile, Molly and Lou's exes, Yona and Olene, have left their pasts behind as they study abroad in France. Together they see springtime in Marseille, find new friendships, and uncover new personal truths. Will their whirlwind trip bloom into a whirlwind romance, or will their journeys to self-discovery put them on different paths entirely?"--